Technical assessment and decision making for the environmental recovery of waterways and their banks: a science-based protocol - Silva, R. A. [UNESP]; Oliveira Afonso, A. A. de; Francescony, W.; Silva, A. M. da [UNESP] (Springer, 2019)
The poor management of aquatic ecosystems often results in environmental degradation, which requires actions for its recovery. A field protocol was elaborated to guide users (restorationists) to assess degraded areas and provide site- and situation-specific interventionist actions. The protocol was developed following the plant or animal taxonomy framework by Linnaeus, considering that the first character has two mutually exclusive possibilities. It was elaborated in three parts: (1) a technical glossary, (2) a hierarchical key, and (3) a set of intervention actions that are indicated according to the case. Complementarily, ten degraded sites (lentic or lotic ecosystem), all located in continental regions of the Brazilian territory, were evaluated using this key. The protocol was thought to be applied to continental and superficial water bodies. It starts separating the lotic and lentic ecosystems, and after each part goes for specific ways, all of them finishing in one or more interventionist action(s). The set of actions presented is composed of fourteen scenarios, seven of them to be implemented on-site, five to be implemented off-site, and two to be implemented on- and/or off-site. The intervention actions range from simply monitoring, to revegetation of the riparian zone, to activities that target the reoxygenation of hypolimnion. The study cases exemplify the use of the key and provide insight into the required adjustments for the implementation of intervention actions. The protocol and guidelines presented here will allow in a systematic manner, assess and compare the outcomes and efficiency of river restoration projects, locally, regionally and internationally.
Keywords: Aquatic ecosystems reclamation; Ecological restoration; Ecosystems repair; River ecotechnology